Team Familiarity, Role Experience, and Performance - Upton, D; Huckman, R; Staats, B (2009)
Much of the literature on team learning views experience as a unidimensional concept captured by the cumulative production volume of, or the number of projects completed by, a team. Implicit in this approach is the assumption that teams are stable in their membership and internal organization. In practice, however, such stability is rare, because the composition and structure of teams often change over time (e.g., between projects). In this paper, we use detailed data from an Indian software services firm to examine how such changes may affect the accumulation of experience within, and the performance of, teams. We find that the level of team familiarity (i.e., the average number of times that each member has worked with every other member of the team) has a significant positive effect on performance, but we observe that conventional measures of the experience of individual team members (e.g., years at the firm) are not consistently related to performance. We do find, however, that the role experience of individuals in a team (i.e., years in a given role within a team) is associated with better team performance. Our results offer an approach for capturing the experience held by fluid teams and highlight the need to study context-specific measures of experience, including role experience. In addition, our findings provide insight into how the interactions of team members may contribute to the development of broader firm capabilities.